(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
This briefing contributes to an ongoing international conversation about restorative practices by examining how restorative justice functions as a peace-building tool in culturally diverse public schools plagued by high incidences of violence. By focusing this briefing on New York City, we are reminded that violence and conflict are not limited to the Global South. We are also reminded that our understanding of the term “violence” must include the less conspicuous, but no less prevalent, forms of violence that we see in our schools today. For the purpose of this briefing and my current research, I define schools as a dynamic and intricate system of interdependent groups (Dunlevy and Proctor, 2011), and I will define school-based violence as the intentional harm caused by any member (or members) of that group through systematic, physical, verbal, or attitudinal aggression. My research intends to address some of the challenges of evaluating restorative practices in school settings, specifically by acknowledging and challenging the tacit ethical assumptions about violence brought to play in school communities though official policy and the value systems of individual community members. As such, I am interested in exploring the implications that culturally-based ethical conflict have for the conceptualization and practice of restorative justice in schools. With this in mind, I propose that restorative practices, including but not limited to, proactive and reactive circles,1 and training for students and staff in restorative conferencing can significantly contribute to neutralizing the multiple and often competing value systems that come to play when a school is faced with issues of violence. Finally, I propose that schools that consistently demonstrate high rates of suspensions due to violent incidences be considered violently divided, as suspension is in and of itself an act of division of community member from the community, and I will subjectively suggest that the impact of this division on our school communities be considered in urgent need of attention from the peacebuilding community.